704 Stress echocardiography: myocardial work 'works'. (8th December 2021) - Cusma, Maurizio; Caminiti, Rodolfo; Parlavecchio, Antonio; Vizzari, Giampiero; Fichera, Nunzio; Mancini, Nastasia; De Sarro, Rosalba; Trio, Olimpia; Manganaro, Roberta; Carerj, Scipione; Di Bella, Gianluca; Micari, Antonio; et al.
Abstract: Stress echocardiography is a widely employed diagnostic technique relying on subjective assessment of left ventricular wall motion and particular expertise. We report a case of a male patient with chronic coronary syndrome, who underwent dipyridamole echocardiography before planned non cardiac surgery. Despite the absence of symptoms and relevant electrocardiographic and wall motion changes, only 2D strain and, especially, Myocardial Work analysis was able to detect abnormalities suggestive of myocardial ischaemia. Thus, coronary angiography was performed, showing critical stenosis of the proximal Circumflex artery, that was treated with angioplasty and drug-eluting stent implantation. Interestingly, the location of strain and myocardial work abnormalities was consistent with the culprit vessel territory. This case highlights the particular usefulness of advanced echocardiographic techniques, especially for the detection of one-vessel coronary artery disease, during stress echocardiography.